Os estudos de Joseph Priestley (1733-1804) sobre a teoria da eletricidade - Oliosi, Elisa Cristina (2010)
In the present thesis we approach some aspects related to the investigative process of Joseph Priestley (1733-1804) about the theory of electricity the theory of two fluids. Priestley was one of the natural philosophers who made countless experiments in order to observe the existence of electricity in various bodies. Theirs experiments were described in many publications such as The History and Present State of Electricity with Original Experiments and Familiar to the Study of Electricity. It‟s possible to verify in these publications how was the process of the construction of the theory of electricity. We seek, therefore, in this work we intend to analyze the course of Priestley‟s thought pointing specifically to his methodology of study which involved theory and practice. In order to do so, we privilege our analysis on the experiments with inanimate bodies to focus how he explained the theory of the two electric fluids